Analisis Keandalan Sistem Proteksi Kebakaran Pada Bangunan Gedung Hotel Royal Asnof Pekanbaru - Rodiatul Fitri; Rian Trikomara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Recent development progress in Pekanbaru is increasing rapidly. This condition is marked by the number buildings that have been built. One of the buildings that have been built is hotel. Each buildings has a risk and potential to fire, that can cause casualties. The research aimed to analyze of building reliability of Hotel Royal Asnof Pekanbaru against fire hazard protection system according to Ministry of Public Works Regulation number 26,2008. This study used Check List form PD-T-11-2005-C (Fire Safety Inspection on Building) and the result from this form is used to get reliability for fire hazard protection system using Analytical Hierarchy Process (AHP) method. The result showed that the reliability of protection system on building Hotel Royal Asnof Pekanbaru according to Check List Method was 88.788 %, while the result calculated by using Analytical Hierarchy Process (AHP) method was 88.125 %, and categorized well, so that the fire protection system on this building is reliable. Keywords: Fire Protection System, Check List Method, Analytical Hierachy Process (AHP), Hotel Royal Asnof.